Hambatan Dan Solusi Terkait Perlindungan Hak Anak Di Palestina Dalam Prespektif Hukum Humaniter Internasional - Ibrahim, Mohammad Makhdum; Meylani, Neyna (Eastasouth Institute, 2024)
This article discusses the protection of children's rights in Palestine, especially children who are victims of war and prisoners of war by Israel, in the context of international humanitarian law. In situations of armed conflict plaguing Palestine, children face various obstacles such as limited access to health and education services, attacks on vital infrastructure, and economic barriers. The implementation of international humanitarian law and human rights in the protection of Palestinian children is still limited, with violations of children's rights often not followed up properly. The research method used is normative research with qualitative analysis of legal principles contained in legal provisions and legal doctrine. This research aims to identify obstacles in the protection of children's rights in Palestine and offer concrete solutions to strengthen the protection of children in armed conflict.